THE COMBINATION OF COLORS "IN THE CONTEXT OF DIGITAL ART": रंगों का संयोजन ‘‘डिजिटल आर्ट के सन्दर्भ में’’ - Garg, Pragati (International Journal of Research -GRANTHAALAYAH, 2014)
While creating the creation, God filled the beauty of the universe with unlimited beauty. It also contains beauty as well as spirituality. Art has been expressing the sentiments of human beings from the creation of the universe itself. Man has been expressing his feelings since time immemorial. As human senses developed, art also matured. All the forms provided by nature and the bizarre emotions and rasas evoked in our minds by the artists through different shelters or bases are embodied with the help of various Karan-implements. Epoch changes with inexorable change, and along with it, traditions, styles, language, forms all change, but the tangible form of soul and heart never changes. Just as colors were valued by the creation of life, colors have remained their dominion ever since. He changed but his main source did not change. The artist has made the plan of this original form the subject, and today he has set the paintbrush of the expressions expressing emotions on the threshold of renewal, which is presented to us in the form of digital art. Prior to the 18th century, there were scientific inventions that changed the nature of art itself, a variety of technological developments that gave the traditional art of modern art a renewal. What is today known as digital art, it is known by many names such as computer art, multimedia art and new media art, under which the colors used in traditional form are presented in a new form by digital technology. Do, which greatly affects the viewer. ईश्वर ने सृष्टि की संरचना करते समय सृष्टि के कण-कण में असीमित सौन्दर्य भर दिया। इसमें सौन्दर्य के साथ-साथ प्राणतत्व भी निहित है। कला मनुष्य के भावों को सृष्टि के सृजन से ही व्यक्त करती आयी है। आदिकाल से मनुष्य अपनी भावनाओं की अभिव्यक्ति करता आया है। जैसे-जैसे मानवीय संवेदना विकसित होती गयी, कला भी परिपक्व होती गई। प्रकृति द्वारा प्रदत्त सारे रूप और उन रूपों द्वारा हमारे मन में उद्बुद्ध विचित्र भाव एवम् रसों का कलाकार भिन्न-भिन्न आश्रयों या आधारों के माध्यम से विभिन्न करण-उपकरणों की सहायता से मूर्त करते हैं। निष्ठुर परिवर्तन के साथ युग बदलता है और उसके साथ-साथ परम्परायें, शैलियाँ, भाषा, रूप सभी परिवर्तित हो जाते हैं परन्तु आत्मा और हृदय का मूर्त स्वरूप कभी नहीं बदलता। जिस प्रकार रंगों का महत्व जीवन के सृजन से हुआ, तब से रंग अपना प्रभुत्व बनाये हुये हैं। उसका परिवर्तन तो हुआ परन्तु उसका मुख्य स्त्रोत नहीं बदला। कलाकार इसी मूल रूप की योजना को विषय बनाकर आज वह भावों को व्यक्त करने वाले तूलिका घातों को नवीनीकरण की ऐसा दहलीज पर खड़ा कर दिया है, जो डिजिटल आर्ट के रूप में हमारे समक्ष प्रस्तुत है। 18वीं शताब्दी से पहले वैज्ञानिकी अविष्कार हुये जिन्होंनें कला के स्वरूप को ही बदल दिया, कई प्रकार के तकनीकि विकास किये जिन्होंने परम्परागत चलते आ रहे कला को एक नवीनीकरण का स्वरूप दिया। जिसे आज डिजिटल आर्ट के नाम से जाना जाता है, इसे अनेक नामों से जाना जाता है जैसे- कम्प्यूटर आर्ट, मल्टीमीडिया आर्ट व न्यू मीडिया आर्ट कहा जाता है, जिसके अन्तर्गत हम परम्परागत रूप में प्रयुक्त रंगों को डिजिटल तकनीक द्वारा एक नये रूप में प्रस्तुत करते हैं, जो दर्शक को बहुत प्रभावित करता है।